Statistics for psychology : a guide for biginners - Watt, Roger (Sage, 2019)
This concise, easy-to-understand and highly visual book helps students to understand the principles behind the many statistical practices. This text helps students to build a mental map to enable them to work their way through tests and procedures with a better level of understanding (and ultimately feel more confident and get better grades). Statistical analysis will also be covered in the book in the same simple-to-follow way, without messy details or complicated formulae. However, this approach does not lead to simple understanding. Instead it allows students to really grasp how to use, and be creative with, statistics.